A META ANALISIS : EFEKTIVITS METODE PEMBELAJARAN BLANDED LEARNING TERHADAP CAPAIAN KOGNITIF SISWA DI ERA DIGITALISASI - Firmansyah Putra (AI Society & STMIK Indonesia, 2024)
This research aims to discuss the effectiveness of the Blended Learning learning method on student learning outcomes. This research is a meta-analysis research using secondary data. The data obtained is in the form of post test results for the experimental class and control class from articles that apply blender learning. The number of articles used in this meta analysis was 15 articles. The data that has been successfully filtered is then calculated using the effect size (ES) formula. The calculation results show that learning using the blended learning method can also improve student learning outcomes. It can be concluded that learning using the blended learning method has a high level of effectiveness and is appropriate for student learning outcomes.